Anastasis: recovery from the brink of cell death. Issue 9 (19th September 2018) - Tang, Ho Man; Tang, Ho Lam
Abstract : Anastasis is a natural cell recovery phenomenon that rescues cells from the brink of death. Programmed cell death such as apoptosis has been traditionally assumed to be an intrinsically irreversible cascade that commits cells to a rapid and massive demolition. Interestingly, recent studies have demonstrated recovery of dying cells even at the late stages generally considered immutable. Here, we examine the evidence for anastasis in cultured cells and in animals, review findings illuminating the potential mechanisms of action, discuss the challenges of studying anastasis and explore new strategies to uncover the function and regulation of anastasis, the identification of which has wide-ranging physiological, pathological and therapeutic implications.